Mucocutaneous acanthosis nigricans in a patient with Crouzon syndrome. - Romiti, R.; Oliveira, Z.N.P. (European Journal of Pediatric Dermatology, 2018)
Crouzon syndrome (CS) is an inherited disorder transmitted by an autosomal dominant trait. lt is characterized by a typical facies due to a craniofacial dysostosis. CS is rarely associated with acanthosis nigricans (AN) of the skin. The Authors report an exceptional case of CS associated with AN, with silmultaneous involvement of the skin and mucous membranes.